(untitled) (Research, Society and Development, 2022)
Ozone (O3), is a gas discovered in 1785 by the Dutch physicist Martinus van Marum, is a molecule composed of three oxygen atoms, highly volatile and unstable, being found naturally in the ozone layer, a layer that protects the planet from radiation. solar. It has been successfully used for over 100 years thanks to its bactericidal, virucidal and fungicidal capabilities, analgesic capacity, biocompatibility, immune system stimulation, in addition to its therapeutic effect that facilitates wound healing, improves sensitivity and blood supply. to the fabric. In the field of dentistry, it has been successfully used in the fight against caries disease, also being used in various means such as endodontics, oral and maxillofacial surgeries, periodontal and gingivitis treatments, as well as palliative treatments for plaque control. Therefore, its main means of administration are via gas, dissolved in water, serum, vegetable oil, or associated with some compound already used in dental procedures such as chlorhexidine and sodium hypochlorite, direct inhalation is not recommended in view of its respiratory tract toxicity.